Strategi Dakwah Penyuluh Agama Islam Kantor Urusan Agama Kecamatan Sidemen dalam Meningkatkan Keimanan Muallaf di Desa Sinduwati Karangasem Bali - Hidayat, Rizal (Fakultas Dakwah UIN KHAS Jember, 2023)
In the realm of preaching, there is undoubtedly a need for specific strategies to ensure that the preaching partners can effectively embrace the preaching process. Since converts are newly embracing Islam, and their faith is still considered fragile, intensive guidance is essential to lead and assist them. The Islamic religious educators have a noble duty to enhance the faith of converts through the employed preaching strategies, aiming to motivate, guide, and instruct them to understand the teachings of their newly adopted religion. The objectives of this research are: 1) To comprehend the preaching strategies of Islamic religious educators in enhancing the faith of converts. 2) To identify the supporting and hindering factors of the preaching strategies employed by Islamic religious educators in enhancing the faith of converts. This research adopts a qualitative research method with a descriptive study design. The findings of this research include: 1) Islamic religious educators employ three preaching strategies, namely establishing the Al-Muhajirin Study Group specifically for converts, providing virtual counseling guidance, and implementing SALAMAH (Joyful Home Services). 2) Three supporting factors are identified, including the widespread lack of awareness among converts about Islam, interfaith marriages, and environmental factors. On the other hand, three hindering factors include the lack of awareness among converts to learn and practice Islamic teachings, the susceptibility of converts to revert to their previous religions, and the influence of peer factors.